Shape Preserving GOl Rational Interpolation. - Majid, A. A; Hussain, M. Z.; M. Ali, M. Ali; M. Piah, A. R. (2009)
A GCl rational quartic function has been constructed with three parameters to preserve the shape of positive and monotone curve data. Simple data dependent constraints are derived on one of the parameters to preserve the shape of data while other two are free to refine the shape of curve at user choice.